2022
DOI: 10.3389/fenrg.2022.849949
|View full text |Cite
|
Sign up to set email alerts
|

Performance and Economic Analysis of Organosolv Softwood and Herbaceous Lignins to Activated Carbons as Electrode Materials in Supercapacitors

Abstract: In this work, yellow pine (YP, softwood) and switchgrass (SG, grass) lignins were extracted as a coproduct of an organosolv γ-valerolactone (GVL) biorefinery that also produces biofuels and furfural. The extracted lignins were converted to carbon precursors for synthesizing porous activated carbon electrodes for high energy-density supercapacitors. This research details the impact of lignin composition on the derived porous structures and electrochemical properties of activated carbons. Lignin precursors with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Pretreatments such as organosolv involve solvents that increase the energy requirements and operating costs of the process, decreasing its economic viability. The economic feasibility of organosolv schemes has been widely reported for lignin extraction at the pilot scale [ 69 ]. The kraft and alkaline processes are used at the industrial scale for removing lignin from woody biomass for pulp and paper production.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pretreatments such as organosolv involve solvents that increase the energy requirements and operating costs of the process, decreasing its economic viability. The economic feasibility of organosolv schemes has been widely reported for lignin extraction at the pilot scale [ 69 ]. The kraft and alkaline processes are used at the industrial scale for removing lignin from woody biomass for pulp and paper production.…”
Section: Resultsmentioning
confidence: 99%
“…Although dilute acid pretreatment has been widely discussed in biotechnological applications, its implementation at the industrial scale has been slowed down. These delays are largely due to the generation and accumulation of inhibitory compounds and the high corrosion of processing units and piping [ 69 ]. Therefore, TRL must be analyzed from an operational and design perspective with techno-energetic and economic considerations.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, research on electrode materials has been a hot topic ( Walters et al, 2021 ; Yu et al, 2021 ). Currently, porous carbon spheres are excellent candidates for electrode materials due to their physical morphology, chemical resistance, and well-developed porous structures ( Veerakumar et al, 2020 ; Song et al, 2021 ; Liu et al, 2022 ; Yu et al, 2022 ). The regular spherical shape reduces the resistance of electrolyte diffusion, and the space between the spheres makes the electrode accessible to the electrolyte ( Chen et al, 2014 ; Oschatz et al, 2015 ; Mutuma et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a growing body of research has focused on cheap and renewable biomass resources as supercapacitive electrolytic feedstocks ( Vijayakumar et al, 2019 ; Zhang et al, 2019 ; Xu et al, 2020 ; Peng et al, 2022 ). A multitude of low molecular weight carbohydrates such as lignin, chitosan, glucose, fructose, sucrose, xylose, have been explored to produce PCSs by mild hydrothermolysis ( Saha et al, 2014 ; Xu et al, 2018 ; Gao et al, 2021 ; Hwang et al, 2022 ; Yu et al, 2022 ). But a paucity of studies has reported preparation of porous carbon spheres directly from high molecular weight carbohydrates such as cellulose and hemicelluloses ( Wang and Shi, 2015 ; Hwang et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%